Implementation of the Pancasila Student Profile Strengthening Project through Disaster Mitigation Education - Anjani Putri Belawati Pandiangan; Niksah Uma (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This research study looks at how the project of strengthening students' profiles with Pancasila is implemented through disaster mitigation education at SD Muhammadiyah 2 Sangatta Utara. The implementation of this project aims to build students' ability to deal with disasters, as well as instill Pancasila values that are applied in daily life. The project is implemented as part of a standalone curriculum, focusing on student character development. This research was conducted using a qualitative approach with a descriptive type. Data were obtained through observation, interviews, and documentation and then analyzed using the Miles & Huberman data analysis technique. This study involved five informants: two students, a teacher, a principal, and a vice principal for curriculum. Based on the interviews, this study's results indicate that the project's implementation to strengthen the profile of Pancasila students through disaster mitigation education is very good and enthusiastically followed by students and teachers, which is carried out in various stages. This project involves cooperation with the fire department and aims to instill humanitarian values, cooperation, and independence in students. In addition, the project also involved extracurricular activities that enabled the development of students' interests and talents. This implementation project aligns with the main principles of strengthening the Pancasila student profile, including exploratory, holistic, contextual, and student-centered approaches. Therefore, this research provides an overview of the importance of integrating Pancasila values in education, particularly in addressing disaster risk.